A three-component substitute for tears (Stillavit®) in the prevention of combined dry eye syndrome after cataract surgery: usage experience - I. P. Shurygina; S. N. Akulov; E. V. Kabardina; M. K. Shulikova; S. Yu. Serykh; A. G. Egiazarova (Российский офтальмологический журнал, 2018)
Purpose: to study the possibilities of the three-component substitute for tears (Stillavit®) in the prevention of combined dry eye syndrome after cataract surgery. Material and methods. 60 patients (60 eyes) aged 55 to 82 (ave. 69.7 ± 7.5 years) with subclinical dry eye syndrome of various genesis were operated for cataract. The patients were divided into two clinical groups depending on the type of post-surgical therapy; the main group of 30 patients (30 eyes) who received standard treatment (ophthalmic corticosteroid and antibacterial drugs 4 times a day) and lacrimal replacement therapy with Stilavit® 4 times a day for 7 days, and the control group of 30 patients (30 eyes) who only received standard postoperative treatment for 7 days. Examination setting included biomicroscopу with vital dyes, a Schirmer test, a Norn test, an evaluation of the lacrimal meniscus index, and the degree of epitheliopathy of the conjunctiva and the cornea. Results. Patients with subclinical dry eye syndrome who received corneal surgery with cataract phacoemulsification and IOL implantation are at risk of a complication of the course of dry eye syndrome and the development of a combined dry eye syndrome. Inclusion of the Stilavit® instillation in the early postoperative period 4 times a day for 7 days significantly increases the stability of the pregroovy tear film and lessens the degree of the epitheliopathy of the conjunctiva and the cornea. Conclusions. Based on the examination data, we can recommend a three-component substitute for tears (Stilavit®) for the prevention of the development of combined dry eye syndrome after cataract surgery. For citations: Shurygina I.P., Akulov S.N., Kabardina E.V., et al. A three-component substitute for tears (Stillavit®) in the prevention of combined dry eye syndrome after cataract surgery: usage experience. Russian ophthalmological journal. 2017; 10 (4): 82-8. doi: 10.21516/2072-0076-2017-10-4-82-88 (In Russian).